Students’ curiosity profile in excretion system topic taught using authentic inquiry learning - Kasyfi Rifqi Mouromadhoni; Sri Atun; Sabar Nurohman (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
Curiosity is a basic important aspect encourages students in finding various information which, in turn, aid them to encompass the concept learnt. This descriptive research aimed at elaborating the curiosity profile of junior high school students in science learning, particularly in excretion system topic who were taught using the authentic inquiry learning. This research was conducted at SMP Negeri 14 Yogyakarta with 32 of eight graders as the subjects. The instrument used was curiosity response questionnaire. The data obtained was analyzed using percentage. The results showed that the average of curiosity achievement obtained was categorized as strong (75%). However, the comparison of implementations between the authentic inquiry learning and the other learning models are needed to get more comprehensive information.